A STUDY OF THE CORRELATION BETWEEN ACCOUNTING DISCLOSURE AND FINANCIAL REPORTING QUALITY IN BANKS REGISTERED IN THE IRAQI STOCK MARKET - Abboud Jadaan Hamad; Prof. Dr. Emna Boumediene (American Journals, 2023)
The research aims to identify both accounting disclosure and financial reporting quality (FRQ). It also aims to measure the role of accounting disclosure in enhancing the FRQ of banks listed in the Iraqi stock market (ISM). The study was conducted on Al-Iraq Commercial Bank, Gulf Commercial Bank, and Ashur International Bank. A questionnaire was received from sample of 177 individuals. SPSS V24 and Amos V24 were used for data analysis, including measures such as mean, standard deviation, coefficient of variation, frequencies, and percentages. The study found that disclosing accounting information helps achieve more transparency, creating a positive perception among stakeholders towards the banks and reducing their resistance to changes initiated by bank management. Providing appropriate information to stakeholders clarifies the bank's policies, plans, and activities, allowing them to evaluate and contribute to their improvement for the benefit of all stakeholders. Based on the findings, the researchers recommend the issuance of a direct standard by the Iraqi Accounting and Auditing Standards Board for disclosing non-routine profits and losses.
Keywords: Accounting information, disclosure, financial reports, financial statements, financial reporting quality.